16 - The Socio-economic Crisis in Southern Africa (Botswana, Malawi, Zambia, Zimbabwe) - Guy Mhone, (Africa Development, 1996)
This foregoing paper is intended to be an interpretation and synthesis of developments in the four countries discussed and in the sub-region based on various previous papers written in the Southern Africa Political Economy Monthly (SAPEM) by the author on the output of projects of the Southern Africa Regional Institute for Policy Studies (SARIPS) of SAPES Trust, and on country up-dates of socio-economic trends of the four countries discussed prepared by Richard Kamidza, a Research Assistant at SARIPS.